Perawatan Konservatif Rehabilitasi Khusus Terintegrasi yang Komprehensif Untuk Skoliosis Remaja Idiopatik - Regina Emmanuela Gusti Pratiwi (Syntax Corporation Indonesia, 2022)
Scoliosis is an abnormal lateral curvature of the spine associated with or without rotation of the vertebrae. Scoliosis is not just a cosmetic problem, but it has impact on many aspects of a person’s quality of life. One’s can experience pain, posture, respiratory, psychosocial problems. In This case report we would like to demonstrated an integrated comprehensive, tailor-made rehabilitation treatment for adolescent scoliosis. The patient is a 15-year-old female with complaints of scoliosis and back pain. Her first menarche was when she was 11 years old. No medical Problem was found. She loved to hang out with her friends and family but since her back hump getting worse, she ashamed of herself and sometimes refused to meet them or cover it with thick layer clothes. The pain in scale of 6 has been present for 1 year. She is unhappy with her body alignment and posture. From physical examination we found The Adam forward bend test was positive. From the x-ray before treatment showed the cobb angle was 20. Pelvic tilt (+), Risser sign 3-4, with Scoliosis C Curve. She can easily do her activities without feeling easily tired nor dyspnoea. She was prescribed a tailor-made Boston brace, physical exercise, heating modality, psychosocial intervention. After 12 weeks of therapy and bracing there was an improvement in posture, minimal pain (3-4), and she became more confidence and happy. The spine malalignment and the curvature can compress spinal disks, irritate nerve, strain joints, tighten muscles and it leads to pain. Because of this spine malalignment can affect posture it can leads to a psychosocial problem. Since the cobb angle was 20 degrees, no full maturation found, it is indicated for Brace prescription, to correct posture and prevent progressivity of curve angle. A proper exercise with heating modality can decrease muscle spasm and pain, maintain flexibility and strengthen spine/core muscle. The earlier diagnosis and treatment of an adolescent scoliosis can give so much different; it depends on the maturation and the cobb angle. In this comprehensive treatment needs a support not only from the patient but also from her society.